Responses of dead forest fuel moisture to climate change. Issue 2 (29th August 2016) - Liu, Yongqiang
Abstract: Forest fuel moisture is an important factor for wildland fire behavior. Predicting future wildfire trends and controlled burned conditions is essential to effective natural resource management, but the associated effects of forest fuel moisture remain uncertain. This study investigates the responses of dead forest fuel moisture to climate change in the continental United States, one of the global regions with frequent wildfire and controlled burning activities. Moisture content was calculated for dead fuels with 1‐ and 1000‐hr lags (MC1 and MC1000 ) using the algorithms from the U.S. National Fire Danger Rating System. A set of dynamically downscaled regional climate change scenarios provided by the North American Regional Climate Change Assessment Program was used. The present fuel moisture shows large seasonal variations peaked in winter and spatial variability with dominant meridional change in winter and zonal change in summer. Fuel moisture is projected to decrease overwhelmingly across the United States, mainly caused by temperature increases. The largest MC1 decrease of over 1% mainly occurs in the southwestern United States in spring and southeastern United States in summer, while the largest MC1000 decrease of over 1.5% occurs in the southwestern United States in spring and in the southern Plains and eastern United States in summer. The spatial patterns and seasonal variations of future fuel moisture trends, however, vary considerably with regional climate change scenarios. The drying fuel trends suggest that frequency, size, and intensity of wildfires would increase and prescribed burning windows would decrease in the future in the Southwest and the inter‐mountains during spring and the Rocky Mountains during summer if other fuel conditions remain the same. These results highlight the general vulnerability of semiarid forests to drying fuels trends.